Lipid lowering and additional pleiotropic effects of statins - Ali Çoner; Ahmet Aslan (Acta Medica Alanya)
Statins are among the most commonly prescribed drugs worldwide today. They are primarily effective in primary and secondary prevention of cardiovascular diseases with their cholesterol-lowering properties. Recent studies have reported that statin derivatives have positive outcomes in different clinical conditions with different mechanisms, in addition to their lipid-lowering effects. In this paper, we aimed to discuss the pleiotropic effects of statins in addition to their protective effects in cardiovascular practice.